2019
DOI: 10.1016/j.isci.2019.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Glucose-Induced Cyclic Lipopeptides Resistance in Bacteria via ATP Maintenance through Enhanced Glycolysis

Abstract: SummaryCyclic lipopeptide (CLP) antibiotics have a mechanism that causes membrane malfunction. Thus mechanisms of bacterial resistance to CLPs are thought to modify cell surfaces. However, we found that bacterial resistance to CLPs was strongly related to energy metabolism. Using polymyxin B (PB) as a model of CLPs, we showed that PB causes malfunction of respiration and serious depletion of ATP, contributing to PB-induced cell death and carbon starvation. Glucose addition could maintain the intracellular ATP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 27 publications
3
10
0
Order By: Relevance
“…Glycolysis is the key process for energy production. Various metabolomics and proteomics analyses showed that glycolysis pathway was downregulated in antibiotic stress conditions (Stokes et al, 2019;Yu et al, 2019). In the present work, we observed that most of the altered proteins in glycolysis pathway were downregulated in simvastatin-treated samples (Figure 8a).…”
Section: Glycolysis and Pyruvate Metabolismsupporting
confidence: 63%
“…Glycolysis is the key process for energy production. Various metabolomics and proteomics analyses showed that glycolysis pathway was downregulated in antibiotic stress conditions (Stokes et al, 2019;Yu et al, 2019). In the present work, we observed that most of the altered proteins in glycolysis pathway were downregulated in simvastatin-treated samples (Figure 8a).…”
Section: Glycolysis and Pyruvate Metabolismsupporting
confidence: 63%
“…Our findings are consistent with previous studies on Bacillus and Staphylococcus spp . showing that polymyxin B dysregulates OXPHOS, leading to ATP depletion, which could be reversed by substrate-level phosphorylation 62 , 63 . The authors of these studies concluded that the increased dependence on glycolysis to produce ATP induces drug resistance.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, recent studies on Bacillus and Staphylococcus spp. showed that glycolysis can reverse polymyxin B-mediated ATP depletion that resulted from dysregulation of OXPHOS [ 68 , 69 ]. Secondly, H 2 S can directly target enzymes in the glycolytic pathway through persulfidation to modulate their activity [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%